Pengaruh BIAYA PROMOSI, BIAYA PENDIDIKAN PELATIHAN, DAN RENCANA STRATEGIS PEMERINTAH TERHADAP MARKET SHARE PERBANKAN SYARIAH DI INDONESIA - Molbi Harsanto (Jurnal Manajemen Bisnis dan Keuangan, 2020)
Studies in this research is about The Influence of Promotion Cost, Education and Training Cost, and Government’s Strategic Planning toward Market Share of Islamic Banking in Indonesia in wellbeing perspective. This research used regression analysis with 1 period lagged of dynamic model. This analysis was used to figure out how big the influence of promotion cost, education training cost, and government’s strategic plan as independent variable toward market share as dependent variable, and how deep of wellbeing value (θ/β) that came from learning process of recent period. This article used secondary data, taken from 77 months period of January 2009 up to June 2015. The result of this analysis show us that the significant influence of each variable toward sharia banking’s market share do exist in small number, though. (1) Eventually, promotion cost, education and training cost, and government’s strategic plan influence the market share significantly; (2) The wellbeing value of these three independent variable toward sharia banking’s market share is still low, θ/β as much as 0,04 (still approach 0 (zero)). Furthermore, by going deeper into this result of analysis, it is really expected that all of entities, regulator, academics, customer, and society respect and honor the tawhidy, obedience, usefulness, and moral/ethics in empowering Indonesia sharia banking for more better position. Key words: promotion cost, education and training cost, strategic planning, and market share.